Anatomical characteristics of teats and premilking bacterial counts of teat skin swabs of primiparous cows exposed to different types of bedding (2016)
ABSTRACT: Bacterial populations of teat skin are associated with risk of intramammary infection and may be influenced by anatomical characteristics of teats. The objective of this study was to evaluate associations of selected anatomical characteristics of teats with bacterial counts of teat skin of cows exposed to different types of bedding. Primarily primiparous Holstein cows (n = 128) were randomly allocated to 4 pens within a single barn. Each pen contained 1 type of bedding [new sand (NES), recycled sand (RS), deep-bedded manure solids (DBMS), and shallow-bedded manure solids over foam core mattresses (SBMS)]. During a single farm visit udders (n = 112) were scored for hygiene and 1 front (n = 112) and 1 rear teat (n = 111) of each enrolled cow were scored for hyperkeratosis (HK). Teat length, teat barrel diameter, and teat apex diameter were measured and teat skin swabs were systematically collected for microbiological analysis. Linear type evaluation data for udders of each cow were retrieved for each cow. Teat position (front or rear) was associated with occurrence of clinical mastitis during the 12 mo before the farm visit and more cases occurred in front quarters. The proportion of udders that were classified as clean (score 1 or 2) was 68, 82, 54, and 95% for cows housed in pens containing NES, RS, SBMS, and DBMS, respectively. No association was found between HK score and teat position and no association was found between HK score and teat skin bacterial count. Bacterial counts of teat skin swabs from front teats of cows in pens containing RS and SBMS were significantly less than those of rear teats of cows in pens containing DBMS or NES. Teat skin bacterial counts were significantly greater for swabs obtained from teats of cows with udder hygiene scores of 3 and 4 as compared with swabs obtained from cows with cleaner udders. Of all udder conformation traits evaluated, only narrower rear teat placement was positively associated with bacterial counts on teat skin.